2012
DOI: 10.1093/icesjms/fss023
|View full text |Cite
|
Sign up to set email alerts
|

The relative importance of shallow and deep shelf spawning habitats for the South African chokka squid (Loligo reynaudii)

Abstract: Roberts, M. J., Downey, N. J., and Sauer, W. H. 2012. The relative importance of shallow and deep shelf spawning habitats for the South African chokka squid (Loligo reynaudii). – ICES Journal of Marine Science, 69: 563–571. It is well known that the spawning grounds of chokka squid Loligo reynaudii lie along the shallow inshore regions of South Africa's south coast. However, egg masses have been found in deeper water on the Agulhas Bank, and hydroacoustic targets deemed to be large aggregations of spawning squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…This was preliminarily addressed to a limited degree in the present study by dividing the shelf into two broad release subareas, but this is unlikely to reasonably capture the variability of transport trajectories within the shelf. For instance, larval transport IBM studies of chokka squid (Loligo reynaudii d'Orbigny, 1839) paralarvae off the South African eastern coast, where the location of the spawning grounds is well known (Sauer et al, 1992;Roberts et al, 2012) showed that the release areas were the most important explanatory variable in the models (Martins, 2009;Martins et al, 2010a). Furthermore, dispersal and retention patterns changed cross shore, with the former being important for paralarvae released on the mid-shelf and the latter important for those released inshore.…”
Section: Limitations Of the Simulationsmentioning
confidence: 99%
“…This was preliminarily addressed to a limited degree in the present study by dividing the shelf into two broad release subareas, but this is unlikely to reasonably capture the variability of transport trajectories within the shelf. For instance, larval transport IBM studies of chokka squid (Loligo reynaudii d'Orbigny, 1839) paralarvae off the South African eastern coast, where the location of the spawning grounds is well known (Sauer et al, 1992;Roberts et al, 2012) showed that the release areas were the most important explanatory variable in the models (Martins, 2009;Martins et al, 2010a). Furthermore, dispersal and retention patterns changed cross shore, with the former being important for paralarvae released on the mid-shelf and the latter important for those released inshore.…”
Section: Limitations Of the Simulationsmentioning
confidence: 99%
“…Spawning in the deep was confirmed, mapped and quantified as comprising 18% of total spawning. Experimentation has demonstrated the viability of this spawning through the production of healthy hatchlings (Oosthuizen and Roberts 2009;Roberts et al 2012 Figure 3). This regional pattern of morphological divergence occurred despite high gene flow.…”
Section: Proposed New Life-cycle Scheme For Chokka-squidmentioning
confidence: 99%
“…The most important region for both spawning and fishing is over the Agulhas Bank between Plettenberg Bay and Algoa Bay [7,8] (Fig. 1).…”
Section: Distribution and Biology Of Chokka Squidmentioning
confidence: 99%
“…In about 1984, it was realised that catching and exporting of squid could be a lucrative business and this led to the establishment of the commercial squid jig fishery which developed rapidly from 1985 onwards driven by high demand and good catches [13,14]. Effort was initially concentrated inshore on the spawning aggregations at depths of no more than 40 m, but advancement in technology and upgrading of vessels allowed fishing to move offshore onto the feeding grounds, thus enabling catches to be made throughout the year [8].…”
Section: History Of the Fisherymentioning
confidence: 99%